Influence of socio-demographic characteristics on different dimensions of household food insecurity in Montevideo, Uruguay - Máximo Rossi; Zuleika Ferre; María Rosa Curutchet; Ana Giménez; Gastón Ares (Global Labor Organization (GLO), 2017)
Using a cross-sectional survey with a representative sample of households from the metropolitan area centered on Montevideo, we evaluate first the factorial structure of the Latin American & Caribbean Household Food Security Scale (ELCSA) with an exploratory factor analysis. Secondly, using a probit model we study the influence of socio-demographic characteristics on each of the identified dimensions of the food insecurity. The percentage of affirmative responses to the items of the ELCSA scale ranged from 31.7% to 4.4%. Two factors were identified with the exploratory factor analysis from households without children under 18 years old, whereas three factors were identified for households with children. The identified factors were associated with different severity levels of food insecurity. Likelihood of experiencing different levels of food insecurity was affected by individual characteristics of the respondent as well as characteristics of the household. Household income had the largest influence on all the dimensions, which indicates a strong relationship between income and food insecurity.
Keywords: I14; I31; D12; 330; food security; income; factor analysis; Latin America